The Artistic Response of Bustaman Village Society to Dance Performance in Tengok Bustaman Tradition - Adi Prasetyo, Alfian Eko Widodo; Cahyono, Agus; Jazuli, Muhammad (Catharsis, 2018)
Tengok Bustaman Tradition is a kind of art tradition in Bustaman village held once a year with various show performances, one of them is dance. The tradition of Tengok Bustaman is pioneered by Hysteria community where the aim is to address the city's issues with art as one of its approaches to build an artistic response in Bustaman society. Hysteria is a community that engages in city-sensitive research and with art as its approach. The formulation of the problem in this research is to explain the form of dance performances in Tengok Bustaman tradition, the function of dance performance in Tengok Bustaman tradition and artistic response in Bustaman village. This study uses a qualitative method. This research is studied through interdisciplinary approach named Performance Studies and Sociology of Art. The data collection techniques used are observation, interviews, document studies, and recording techniques. The validation technique uses source triangulation. The data analysis procedures include data reduction, data presentation, and conclusions. The results show that the form of performances in Tengok Bustaman tradition is a dance performance. Dance performance in Bustaman village includes several processes such as pre-performance, performance and after performance. The function of dance performance in Bustaman Village is as the cause of educational media, entertainment media, and communication media and as a commercial media. The existence of dance performance in Tengok Bustaman tradition produces several artistic responses, among others are visual response, auditive response and environmental response. The dance performance in Tengok Bustaman tradition is able to provide changes and development of the village for the better future.